Customer response power capability to enhance marketing performance in Micro, Small and Medium Enterprises (MSME) - Ambar Lukitaningsih; Ida Bagus Nyoman Udayana; Syamsul Hadi; Anis Marjukah; Laurensia Aptik Evanjeli (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
Micro, Small, and Medium Enterprises (MSME) are of importance in the success and growth of Indonesia's national economy. These enterprises form the backbone of the workforce and their marketing performance is a key indicator of progress. However, studies by marketing experts indicate a disagreement between the outcome of market sensing capability and marketing performance. Based on several reports, a sales team that can see the market ahead of time impacts marketing personnel's performance. In contrast, other marketing experts discovered that market sensing quality does not hold such influence. Therefore, this study aimed to resolve the controversy surrounding the investigation by proposing a new concept, such as customer response quality, using a theoretical model. The participants included were 259 MSME actors in Yogyakarta, selected through purposive sampling. Furthermore, questionnaire, data were collected and analyzed using SEM. The results showed that customer orientation, learning orientation, and market sensing quality significantly and positively affected customer response quality. Among these, learning orientation has the most considerable influence. The novelty of this study is that customer response power capability had a significant positive effect on marketing performance. Meanwhile, customer orientation, learning orientation, and market sensing quality had no direct impact, therefore, it was recommended that MSME should focus on the company's ability to sense market quality, customer orientation, and learning orientation to respond to customers, and subsequently increase marketing performance.